Hudā versus Maqāṣid? Teleological Competition in Al-Hidāyāt Al-Qur’aniyyah: Dirāsah Ta’shīliyyah (Vols. I–II) - Muhammad Hariyadi; Zuhrupatul Jannah; Ainun Nadzifah; Zakiyatul Fitriyah (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2026)
Purpose oriented readings of the Qur’an often articulated through maqāṣid (objectives) have become increasingly visible in reform-oriented discourse, yet the scholarly status of maqāṣid Al-Qur’an remains contested and still in the making. Against this backdrop, Al-Hidāyāt Al-Qur’aniyyah, a large institutional initiative affiliated with Umm Al-QuraUniversity, proposes a guidance centered (hudā) program that systematizes verse level “guidance” (hidāyāt) as actionable outputs. This article offers a contrastive comparison between hudā  and maqāṣid centered programs using a qualitative, text centered approach. The primary corpus is Al-Hidāyāt Al-Qur’aniyyah: Dirāsah Ta’shīliyyah (Vols. I–II), read as the project’s programmatic self-articulation; the comparator corpus is maqāṣid Qur’ān programmatic literature, with particular reference to Al-Maqāṣid Al-Kubrā li-l-Qur’ān, which distinguishes major objectives from detailed Guidance (tafṣīlī/ʿamalī). The findings reconstruct four epistemological patterns in Al-Hidāyāt, hudā as telos, non-operationalization of a maqāṣid hierarchy, Salaf authorized epistemic layering, and an applicative output genre and show, via the comparator’s own taxonomy, how maqāṣid and hidāyāt differ in object of inquiry, scale, inferential routes, and extensibility. A worked textual example (Q 2:275–279) demonstrates how each program scales normative output from the same passage. The article contributes a comparator grounded framework for studying teleological competition in contemporary Qur’anic hermeneutics and highlights the growing role of institutional infrastructures in shaping exegetical authority.